Implementasi Metode Design Sprint dalam Perancangan UI/UX Aplikasi Golek Kost Berbasis Mobile - Nur Ifani Khoirunisa; Erika Ramadhani (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The city of Yogyakarta is known as the City of Students or the City of Education because of the many educational centers that stand there. This has made students from outside the region interested in studying in Yogyakarta. The large number of students studying in Yogyakarta makes many people in Yogyakarta open boarding and renting businesses which is a necessity for students from outside the region who come to take their education. The difficulty in finding a boarding house or renting a place that fits the needs is the main obstacle faced due to the lack of information received. In the current era, the digitization process has developed rapidly because most people spend their time holding smartphones, so many mobile-based applications can help with all their needs and needs. One of them is a boarding house search application, e-commerce, and delivery services. However, these three service features are not yet in one application. This makes Golek Kost want to create a mobile-based application that consists of these three features, to make it easier for students to search for boarding houses, boarding furniture, and transportation/moving services. The method used in designing the Golek Kost application is the design sprint. In this method there are four stages, namely: understanding (understanding), divergent (developing), decide (decide), prototype (create a prototype), and validate (validation). The final result of this research is the validation of the prototype design from the UI and UX side, after getting feedback from potential users. Making this prototype design will be made using Figma tools.